Effect of impact force for dual-hose dry blasting nozzle geometry for various pressure and distance: an experimental work - Mat, Mohamad Nur Hidayat; Asmuin, Nor Zelawati; Md. Basir, Md. Faisal; Goodarzi, Marjan; Hasan, Nor Halim (Springer, 2020)
Dry ice blasting plays an essential role in today’s cleaning industry, where many industry players have used it after realizing its advantages. The disadvantage of dry ice blasting is relatively small kinetic energy and offer less aggressive clean effect, especially for dual-hose nozzle geometry. This project was mainly to study the impact force of nozzle geometry of dry ice blasting concerning pressure and distance variation. The nozzle geometries with optimum size and shape are fabricated based on a recent literature study. The experimental research on the effect of the impact forces on different pressures and distances has been conducted to validate the simulation study. The result shows that the optimum nozzle design gives better performance than a based model. Besides, the optimum distance for dry ice blasting operation is less than 400 mm for the pressure range of 2 bars to 4 bars. This distance gives the maximum value of the impacted force for dry ice blasting operation in the industry.